(untitled) (Research, Society and Development, 2022)
The present research aimed to assess the worker’s perception of the Court of Justice of the State of Goiás (TJGO) regarding the impacts and challenges of teleworking before and after the COVID-19 pandemic. It was a descriptive, exploratory study with a quantitative-qualitative approach based on an unpublished study in the TJGO. The results were described according to the following categories of analysis: sociodemographic profile and analysis of employees’ perceptions of the impacts of teleworking, before and after the pandemic. The results showed that in relation to the age of the servers, they are mostly between 41 and 46 years old. The gender of the interviewees is mostly female. Regarding the role of civil servants, 62.8% are judicial analysts; and 16.7% are court clerks. In the second category, which was the analysis of the worker’s perception of the impacts of teleworking before and after the pandemic, it was noted in the perception of the research subjects if they had already worked in the telework format before the pandemic and 96.2% replied no. 98.7% responded that even before the pandemic, they never asked the TJGO to work in telework. Regarding the teleworking routine, 42.3% of the servers stated they had no difficulty establishing a routine. Of those interviewed, 43.6% fully agree with the quality of the Information and Communication Technology (ICT) available. The service time to the user remotely, in the view of the servers, is satisfactory, in the proportion of 46.2% of the participants who agreed.